2015
DOI: 10.5430/elr.v4n3p13
|View full text |Cite
|
Sign up to set email alerts
|

Improving Students’ Reading Comprehension Achievement by Using K-W-L Strategy

Abstract: The research is done in order to improve students' reading comprehension achievement. The writer uses KnowWant-Learn (KWL) strategy, and the data are obtained from the experimental group and the score of the control group, from the fifth semester students of English department, Faculty of Education of HKBP Nommensen University Medan. The data were analyzed by applying t-test formula and it was found that students' achievement who were taught by applying KWL was higher than those who were taught without applyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 1 publication
2
17
0
1
Order By: Relevance
“…Moreover, the students in that group had positive attitudes toward the use of KWL strategy. These results were in agreement with previous studies that confirmed the positive impact of KWL strategy on the achievement of students and their positive attitudes towards its use (Akkoyunlu & Soylu, 2008;Akily, 2010;Araam, 2012;Bonk & Graham, 2006;Gammill, 2006;Ja'ashan, 2015;Kishta, 2008;Lismayanti, 2014;Ogle, 2005;Osguthorpe & Graham, 2003;Siribunnam & Tayraukham, 2009;Shahin, 2008;Sinambela et al, 2015;Taslidere & Eryilmaz, 2012;Tok, 2008;Zouhor et al, 2017).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the students in that group had positive attitudes toward the use of KWL strategy. These results were in agreement with previous studies that confirmed the positive impact of KWL strategy on the achievement of students and their positive attitudes towards its use (Akkoyunlu & Soylu, 2008;Akily, 2010;Araam, 2012;Bonk & Graham, 2006;Gammill, 2006;Ja'ashan, 2015;Kishta, 2008;Lismayanti, 2014;Ogle, 2005;Osguthorpe & Graham, 2003;Siribunnam & Tayraukham, 2009;Shahin, 2008;Sinambela et al, 2015;Taslidere & Eryilmaz, 2012;Tok, 2008;Zouhor et al, 2017).…”
Section: Resultssupporting
confidence: 92%
“…Where there was a statistically significant difference between the marks of the students' in the experimental group and the students' of the control group in the achievement test in favour of the experimental group. Which confirmed that the KWL strategy has a positive impact on student achievement (Akily, 2010;Araam, 2012;Kishta, 2008;Lismayanti, 2014;Sinambela, Manik, & Pangaribuan, 2015;Siribunnam & Tayraukham, 2009;Tok, 2008;Zouhor et al, 2017). Other studies indicate that through the implementation of the KWL strategy, students are encouraged to be mentally active during the learning process, makes the learning of concepts and topics remembering easier, develop appropriate questions for a particular topic and develop their skills in organizing their prior knowledge of the subject and evaluating their success in learning.…”
Section: Previous Studiesmentioning
confidence: 71%
“…Reading plays an important role in language learning because through reading, the students can obtain new information and experience.According toSeken & Artini (2013)reading is a process of comprehending texts to get information in order to make the reader easy to find the world around them. In line with that, reading defined as meaningful interpretation of printed and written verbal symbols (Sinambela, Manik, & Pangaribuan, 2015). For the beginner students, reading is learning to recognize the printed symbols that represent language in order to respond question aboutcontent of the text.Reading is an important skill that must be mastered by the students because through reading, students are expected to be able to understand more certain knowledge and information.…”
Section: Introductionmentioning
confidence: 96%
“…However, reading also becomes one of complex skills because in reading, the students need to comprehend the information in the text. Comprehending the information is not an easy task for students because comprehension involves understanding the vocabulary, seeing the relationship among words and concepts, organizing idea, recognizing authors" purpose, making judgment and evaluating (Sinambela et al, 2015). According to Khruawan & Dennis (2017), reading comprehension refers to the ability which the students are able to read the text accurately and effectively to get the maximum knowledge and information.…”
Section: Introductionmentioning
confidence: 99%
“…The way of understanding and comprehending the text to get the required information is called reading comprehension. It is supported by Sinambela, Manik, & Pangaribuan (2015) that reading comprehension means understanding what has been read and it involves understanding the vocabulary seeing the connection among concepts and words, organizing idea, recognizing authors' purpose, making evaluating and judgement. Unfortunately, there will always be some problems related to teaching reading comprehension.…”
Section: Introductionmentioning
confidence: 99%